The Phenomenon of Spiritual Alienation: a Phenomenological Study of Students at Ma'had Al-Jami'ah UIN Sjech M Djamil Djambek Bukittinggi - Agil Shodiki Manurung; Ibrahim Hasan Ray (Modern Islamic Studies and Sharia Research, 2025)
The development of digital technology has influenced the way young Muslims access and interpret their spiritual lives. Students at Ma'had Aljamiah UIN Sjech M. Djamil Djambek Bukittinggi live in two spaces simultaneously, namely institutional-based spiritual guidance and the digital reality that is present in their daily activities. This condition raises questions about how digitization affects the religious practices and spiritual awareness of students. This study aims to examine the influence of the digital era on the spiritual practices and understanding of students, explore their experiences of spiritual awareness in dealing with digital technology, and identify strategies used to integrate spirituality with technological developments. This study uses a phenomenological approach with qualitative research methodology through in-depth interviews with students. The results show that digitalization has a dual impact. On the one hand, technology makes it easier for students to access religious studies, broadens their horizons, and supports worship and preaching activities. On the other hand, the rapid and diverse consumption of digital content has the potential to reduce the depth of worship and cause confusion in understanding religious authority. To respond to these conditions, students developed various strategies, such as utilizing digital media positively, building online spiritual communities, applying a critical and selective attitude towards religious content, and continuing to refer to religious guidance and authority within the ma'had environment. This study concludes that digitalization does not automatically weaken the spirituality of mahasantri, but rather becomes a space for adaptation and negotiation that allows for a more contextual strengthening of spirituality when accompanied by awareness, guidance, and adequate digital literacy.